2013
DOI: 10.1002/adsc.201300513
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Oxidative Coupling of 2‐Naphthol Derivatives by Copper‐(R)‐1,1′‐Binaphthyl‐2,2′‐diamine‐TEMPO Catalyst

Abstract: An efficient chiral copper catalytic system [(R)‐(+)‐1,1′‐binaphthyl‐2,2′‐diamine‐copper(I) chloride‐TEMPO] for the asymmetric oxidative coupling of 2‐naphthol derivatives to synthesize enantiomerically enriched BINOL derivatives has been developed with good to excellent enantiomeric excess (up to 97% ee). The addition of a catalytic quantity of 2,2,6,6‐tetramethylpiperidin‐1‐yl oxyl (TEMPO) to the copper‐(R)‐(+)‐1,1′‐binaphthyl‐2,2′‐diamine complex greatly enhanced the reactivity and enantioselectivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…34). 128 In this study it was found that the reaction could proceed with just the (R)-BINAM-CuCl catalyst (where BINAM = 1,1 0 -binaphthyl-2,2 0diamine), but the addition of TEMPO significantly improved the reactivity, enabling these reactions to be carried out at room temperature (rather than 90 1C) in shorter reaction times (2-4 days rather than 7-9 days). A range of 1,1 0 -binaphthol derivatives were prepared in good to excellent yields (77-98%) with enantioselectivities up to 97% ee (depending on the substituents).…”
Section: Carbon-carbon Bond Formationmentioning
confidence: 85%
“…34). 128 In this study it was found that the reaction could proceed with just the (R)-BINAM-CuCl catalyst (where BINAM = 1,1 0 -binaphthyl-2,2 0diamine), but the addition of TEMPO significantly improved the reactivity, enabling these reactions to be carried out at room temperature (rather than 90 1C) in shorter reaction times (2-4 days rather than 7-9 days). A range of 1,1 0 -binaphthol derivatives were prepared in good to excellent yields (77-98%) with enantioselectivities up to 97% ee (depending on the substituents).…”
Section: Carbon-carbon Bond Formationmentioning
confidence: 85%
“…Thus, treatment of 16 with vanadium‐salan complex (10 mol %), Yb(OTf) 2 (5 mol %) in PhCl under oxygen atmosphere at 80 °C only led to decomposition of starting material 17. On the other hand, when 16 was treated with CuCl (5 mol %), BINAM (10 mol %), and TEMPO (10 mol %) under oxygen at RT no product formation was observed 18. We then decided to use a procedure, which we had developed for the synthesis of paecilin A ( 3 ) 12.…”
Section: Methodsmentioning
confidence: 98%
“…[17] On the other hand, when 16 was treated with CuCl (5 mol %), BINAM (10 mol %), and TEMPO (10 mol %) under oxygen at RT no product formation was observed. [18] We then decided to use ap rocedure, which we had developedf or the synthesis of paecilin A(3). [12] First we protected the enol moiety by formation of an enol methyl ether using trimethyl silyl diazomethane in dichloromethane and methanol at room temperature to give 17 a and 17 b in 71 %y ield in a1:2.4 ratio, which were separated by flash chromatography on silica gel (Scheme 5).…”
mentioning
confidence: 99%
“…4 Finally, the homocoupling of 2naphthols bearing carbonyl-substituents at the C3-position using molecular oxygen as terminal oxidant and a catalytic amount of TEMPO (2,2,6,6-tetramethylpiperidin-1-yl oxyl) as a co-catalyst was promoted with a moderate to good atroposelectivity by the Cu/BINAM 3 catalytic system. 5 Importantly, the Cu-catalyzed synthesis of (S)-bisoranjidiol 6a and V-catalyzed synthesis of pigmentosin A and talaroderxines A and B6 b illustrate the synthetic utility of such asymmetric oxidative homocouplings.…”
Section: Ia1 Advances In Intermolecular Oxidative Couplingsmentioning
confidence: 99%